Garcinia dulcis Fruit Extract Induced Cytotoxicity and Apoptosis in HepG2 Liver Cancer Cell Line. (18th October 2015) - Abu Bakar, Mohd Fadzelly; Ahmad, Nor Ezani; Suleiman, Monica; Rahmat, Asmah; Isha, Azizul
Abstract : Garcinia dulcis or locally known in Malaysia as "mundu" belongs to the family of Clusiaceae. The study was conducted to investigate the anticancer potential of different parts of G. dulcis fruit extracts and their possible mechanism of action in HepG2 liver cancer cell line. MTT assay showed that the peel, flesh, and seed extracts of G. dulcis induced cytotoxicity in HepG2 cell line with IC50 values of 46.33 ± 4.51, 38.33 ± 3.51, and 7.5 ± 2.52  µ g/mL, respectively. The flesh extract of G. dulcis induced cell cycle arrest at sub-G1 (apoptosis) phase in a time-dependent manner. Staining with Annexin V-FITC and propidium iodide showed that 41.2% of the cell population underwent apoptosis after 72 hours of exposure of the HepG2 cell line to G. dulcis flesh extract. Caspase-3 has been shown to be activated which finally leads to the death of HepG2 cell (apoptosis). GC-MS analysis showed that the highest percentage of compound identified in the extract of G. dulcis flesh was hydroxymethylfurfural and 3-methyl-2, 5-furandione, together with xanthones and flavonoids (based on literature), could synergistically contribute to the observed effects. This finding suggested that the flesh extract of G. dulcis has its own potential as cancer chemotherapeutic agent against liver cancer cell.